PERTANGGUNGJAWABAN HUKUM TERHADAP TINDAK PIDANA PERTAMBANGAN TANPA IZIN (STUDI KASUS PUTUSAN PENGADILAN TINGGI BANDUNG NOMOR 91/PID.SUS/2023/PT BDG) - Hamid, Irwan Abdul; Sapari, Papang (Neolectura, 2024)
This research aims to examine how regulations concerning Mining Permits for People (Izin Pertambangan Rakyat/IPR) are viewed from a legislative perspective and to analyze the legal considerations of judges when imposing criminal sentences on perpetrators of illegal mining based on Bandung High Court Decision Number 91/Pid.Sus/2023/PT BDG. The research methodology used is normative juridical research, which involves the analysis of secondary data or literature. The findings of this research are as follows: First, permits for mining activities in People’s Mining Areas (Wilayah Pertambangan Rakyat/WPR) with limited area and investment are known as People’s Mining Permits (IPR). Law No. 03 of 2020, which amends Law No. 04 of 2009 on Mineral and Coal Mining, and Government Regulation No. 25 of 2024, which amends Government Regulation No. 96 of 2021 on the Implementation of Mineral and Coal Mining Business Activities, include provisions on People’s Mining, as well as procedures and requirements for obtaining a People’s Mining Permit. Criminal sanctions and further penalties apply to those engaging in mining activities without authorization. Article 158 and Article 164 of Law No. 03 of 2020 concerning the Amendment to Law No. 04 of 2009 on Mineral and Coal Mining contain these provisions. Second, the appeal was based on the fact that the panel of judges at the first level failed to carefully analyze the objections and misinterpreted the indictment articles based on the defense notes and evidence presented by the defendants. Article 158 of Law No. 03 of 2020, in conjunction with Article 55 Paragraph (1) of the Indonesian Penal Code, was a significant consideration for the judges in evaluating the first alternative indictment. According to the judges, this indictment was appropriate and accurate. Concerning the second indictment, Article 107(a) of Law No. 39 of 2014 on Plantations, in conjunction with Article 55 Paragraph (1) of the Penal Code, the High Court Judge stated that the Cibadak District Court Decision Number 365/Pid.Sus/2022/PN Cbd was not entirely accurate. The author argues that in interpreting and establishing Article 158 of Law No. 3 of 2020, which amends Law No. 4 of 2009 on Mineral and Coal Mining, the Public Prosecutor’s demands and the content of the indictment were incorrect.